(untitled) (Journal of Biomedical Investigation, 2025)
Background: Welders are prone to radiation, mechanical and chemical eye injuries which could cause visual loss. Information on the prevalence of ocular disorders among welders is essential for planning eye care services. Aim: To determine the prevalence of eye diseases among welders in Onitsha, Nigeria. Materials and Methods: Eligible welders at Bridge Head Market Onitsha, selected by simple random sampling, had ophthalmic assessment using a pre-tested questionnaire, visual acuity assessment, external eye examination, refraction, and ophthalmoscopy. Results: Two hundred and five adult male welders, aged 18 – 70 years, median - 42 years, were studied. Job experience was 6 months - 35 years, median - 15 years; 70 (34.1%) participants were married. All the participants complained of having had at least one eye disease symptom; light sensitivity, 80 (39.0%), and ocular pains, 62 (30.2%) were the commonest symptoms. Ninety four (45.9%) were diagnosed with ocular disorders; allergic conjunctivitis, 40 (42.5%) and pterygium, 24 (25.5%), ametropia, 12 (12.8%), were the commonest disorders. No participant was bilaterally blind but 13 (6.3%) had monocular blindness caused by corneal opacity, 6 (2.9%), cataract, 4 (2.0%), glaucoma, 2 (1.0), and pterygium, 1 (0.5%). Twenty-nine (14.1%) had moderate low vision and 30 (14.6%), severe low vision in the better eyes. Conclusion: The prevalence of eye diseases, low vision and monocular blindness among the welders are high but the causes are avoidable. Eye health education for welders is recommended.